2009
DOI: 10.1007/s12519-009-0043-0
|View full text |Cite
|
Sign up to set email alerts
|

Delayed presentation of congenital diaphragmatic hernia with intrathoracic gastric volvulus

Abstract: GV is a clinical emergency which can be life-threatening for children. Upper gastrointestinal study and CT scan with contrast meal are helpful in the diagnosis of the lesion. We emphasize prompt surgical therapy to avoid gastric necrosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2014
2014
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…A plain abdominal x-ray and an upper gastrointestinal contrast study are useful for diagnosis. Some studies suggest that either CT or MRI are necessary for the correct diagnosis [ 5 ] but in our experience if the diagnosis is clear with plain X-ray contrast studies, surgical treatment should not be delayed with further complementary imaging tests. The standard treatment for volvulus is open laparotomy with detorsion and prevention with anterior gastropexy [ 4 ], as performed in our case.…”
Section: Discussionmentioning
confidence: 95%
“…A plain abdominal x-ray and an upper gastrointestinal contrast study are useful for diagnosis. Some studies suggest that either CT or MRI are necessary for the correct diagnosis [ 5 ] but in our experience if the diagnosis is clear with plain X-ray contrast studies, surgical treatment should not be delayed with further complementary imaging tests. The standard treatment for volvulus is open laparotomy with detorsion and prevention with anterior gastropexy [ 4 ], as performed in our case.…”
Section: Discussionmentioning
confidence: 95%
“…A plain abdominal x-ray and an upper contrast study are useful for diagnosis. Some studies suggest that either computed tomography or MR are required for the correct diagnoses[ 4 ] but in our experience if the diagnosis is clear with plain X-ray contrast studies, surgical treatment should not be delayed with further complementary imaging tests.…”
Section: Discussionmentioning
confidence: 96%
“…The stomach is fixed by four ligaments (gastrocolic, gastrohepatic, gastrophrenic and gastrosplenic ligaments) and anomalies in these ligaments may increase the chance for the presence of a gastric volvulus. [ 3 ] In patients with diaphragmatic defect (CDH, diaphragmatic eventration, hiatal hernia) the gastric fixation can be elongated or absent,[ 4 ] as this ligaments are normally inserted in the diaphragm,[ 2 ] thus making this is a predisposing factor for an abnormal stomach rotation. [ 5 ]…”
Section: Discussionmentioning
confidence: 99%
“…The association of HPS with chronic gastric volvulus and diaphragmatic eventration has been reported [5,6]. In addition, the association of diaphragmatic hernia with gastric volvulus has been reported [10,11]. Kotobi et al found congenital diaphragmatic hernia in 65% of the children with acute gastric volvulus, and 84% of those aged less than 1 month [10].…”
Section: Case Reportmentioning
confidence: 99%